Analysis for the Policy of Reorganizing Rural residential patches in China and the Dilemma of Ecological Niche in China’s Urban and Rural Areas - Yue, Yufeng; Li, Weiqiang Wang Jian (AESOP, 2015)
With the rapid economic development and significant urbanization in China, dual-structure phenomenon, caused by the great gap of development level in urban and rural areas, has become increasingly prominent. Compared with the urban areas, the development in terms of social, economic and cultural aspects in rural areas has encountered underlying dilemma. To narrow the gap between urban and rural development, the Ministry of Land and Resources has proposed planning policy for reorganizing rural lands, trying to achieve integration of the population and land resources in agricultural areas and construction of modern intensive rural residential areas to promote the overall development in urban and rural areas, and realize the modernization goals for the benefit of rural areas, agriculture industry and peasants there. This paper is aimed to adopt the research perspective and method of ecological niche theory, establish the ecological niche expansion model and analyse the theory essence of the Reorganization of rural residential patches to summarize the internal change mechanisms of the ecological niche in urban and rural areas during the process of consolidation. Combined with author’s planning and research in Henan Province, Chinese agricultural populous province, the empirical analysis could be conducted to determine the niche development trend in urban and rural areas during the course of the consolidation, so as to propose a value judgment orientation for China rural governance and planning policy development, as well as the discussions on the niche dilemma and path direction of the rural development in China.
Book of proceedings: Annual AESOP Congress, Definite Space – Fuzzy Responsibility, Prague, 13-16th July, 2015